What have we learned from teaching conferences and research on learning in biomechanics? - Knudson, D. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
A narrative review was conducted of biomechanics teaching/learning papers published in teaching conference proceedings and in journals since 1980. The majority of the papers published focused on course concepts and technology, rather than reporting data on student learning. Recent progress has been made in standardized tests of biomechanical concepts and identifying factors that are associated with learning these concepts. Future research should use these tests to focus on learning-related factors and active learning strategies from physics education research to improve student mastery of biomechanical concepts.